Arrival of New Great Salinity Anomaly Weakens Convection in the Irminger Sea. Issue 11 (9th June 2022) - Biló, T. C.; Straneo, F.; Holte, J.; Le Bras, I. A.‐A.
Abstract: The Subpolar North Atlantic is prone to recurrent extreme freshening events called Great Salinity Anomalies (GSAs). Here, we combine hydrographic ocean analyses and moored observations to document the arrival, spreading, and impacts of the most recent GSA in the Irminger Sea. This GSA is associated with a rapid freshening of the upper Irminger Sea between 2015 and 2020, culminating in annually averaged salinities as low as the freshest years of the 1990s and possibly since 1960. Upon the GSA propagation into the Irminger Sea over the Reykjanes Ridge, the boundary currents rapidly advected its signal around the basin within months while fresher waters slowly spread and accumulated into the interior. The anomalies in the interior freshened waters produced by deep convection during the 2017–2018 winter and actively contributed to the suppression of deep convection in the following two winters. Plain Language Summary: The Subpolar North Atlantic is prone to recurrent extreme freshening events (i.e., when the salinity decreases abruptly) called Great Salinity Anomalies (GSAs). As the circulation spreads them around the subpolar region, they indirectly contribute to the reduction of deepwater formation and weakening of the vertical transport of heat and anthropogenic carbon dioxide in the ocean. Here, we combine historical and new moored temperature and salinity records to document the arrival, spreading, and impacts of the most recent GSA in the Irminger Sea. This GSA led to a rapid freshening of the Irminger Sea between 2015 and 2020, 2–4 times faster than the freshening rates registered in the previous 10 years. This event culminated in annually averaged salinities as low as the freshest years of the 1990s and possibly since 1960. Tracking the GSA's path in the subpolar gyre, we found that the GSA flows with the boundary currents along the basin's rim within months while other processes slowly spread the fresher waters to the central Irminger Sea. The accumulation of fresher waters in the basin's center freshened the deep water formed during the 2017–2018 winter and actively contributed to the halt of deepwater formation in the following two winters. Key Points: Fresh anomaly identified in the Iceland Basin exhibits characteristics of a Great Salinity Anomaly (GSA) as it spreads into the Irminger Sea Within the Irminger Sea, the GSA was rapidly advected by the boundary currents while slowly spreading to the basin center Extreme freshening played a significant role in suppressing deep convection in the Irminger Sea during the 2018–2019 and 2019–2020 winters